Investigating the stakeholder engagement indicators towards renewable energy projects success in Malaysia - Zarith Sufia, Azlan; Muhammad, Waris; Puteri Fadzline, Muhamad Tamyez (BP Services, 2020)
Stakeholder engagement has been acknowledged as being a vital approach in delivering successful project outcomes. However, there is a limitation of studies on how the stakeholder engagement can indicate the successful implementation of renewable energy projects. The purpose of this study is to fill the gap by investigating the influence of stakeholder engagement indicators towards renewable energy project success. This study suggests second-order model by extending stakeholder engagement indicators as hierarchical and integrating ten associated components. Data was collected through survey questionnaires applied to the Renewable Energy Power Providers (REPPs) in Malaysia, using stratified random sampling. SPSS ver.23 and Smart PLS 3.0 software was applied to test measurement and structural models of this study. The findings revealed that stakeholder relations, stakeholders’ communication, stakeholders’ learning and stakeholder integration were positively significant towards the renewable energy project success. It is apparent that this study allows contribution to the body of knowledge of project management and offers some important insights into limited literature on stakeholder engagement.This study also sheds light on the key stakeholders’ groups in developing successful renewable energy projects.